Power Generation From Biomass Fluidized Bed System - Abdullah, Abdul Halim (Universiti Sains Malaysia, 2005)
Present energy use is largely dependent on fossil fuels which make future sustainable development very difficult. Fossil fuels contain high amount of carbon dioxide (CO2) and sulphur dioxide (SO2) that may cause air pollution and global warming. Biomass fuels appear as the most suitable option to substitute the fossil fuels with the highest general worldwide potential. Fluidized Bed Gasifier (FBG) is one of the conversion techniques that can be used to converse the biomass into useful and clean gasses. This system has been designed at Universiti Sains Malaysia for researching process related. The present work reports studies on the previous researches on fluidized bed and the development process of the designed system. The design parameters of fluidized bed are also studied for further understanding. The development process is including the piping installation of the system and the modification of the system. The modifications carried out depending of the problems occur after the piping installation. Most of the modification carried out focused on the gas inlet port connection. Besides, some experiments are also carried out in order to determine the bed material (sand) size, the density and the moisture content of wood chip fuel. Sands and wood chip are used in running the gasifier system. The results of the experiment then are compared with the design parameter to ensure either the sand purchased suitable for the gasifier experiment or not.